Electron microscopy of the conformational changes of alpha 2-macroglobulin from human plasma - Tapon-Bretaudiére, Jacqueline (1985)
High resolution electron microscopy reveals that fully active alpha 2-macroglobulin (α2M) from fresh human plasma presents a very characteristic tetrameric structure. This native conformation of the α2M molecule is described here for the first time, along with its various orientations in negatively stained preparations. Although the native form is sensitive to inactivation, glutaraldehyde fixation is not necessary for its observation except when ammonium salts are used. The tetrameric structure of α2M undergoes a drastic conformational change when the protein is treated either with trypsin, thrombin or methylamine, as evidenced by the appearance of the typical)+(structure already described in the literature. The various aspects of this second conformation correspond to different orientations of the molecules in the stain film, and depend upon the nature of the support.